(untitled) (Libellarium: journal for research in the field of information and related sciences, 2011)
This paper aims at investigating various approaches to the study of prayer-books and catechisms, i.e., material that is generally included in religious literature and linked to the Church and its teachings. The introduction of the paper contains definitions of prayer-books and catechism, their types and differences. In the second part of the paper, the search results of three largest collective catalogues in Croatia (Crolist, MetelWin and Zaki) were presented, followed by search results of the National and University Library Catalogue, Croatian Scientific Bibliography and HRČAK portal so as to gain insight into literature dealing with prayer-books and/or catechisms with an aim to highlight fields and branches of science dealing with such publications. Literature returned in the search results was analysed in terms of subject and based on Universal Decimal Classification markings, fields and branches of science, i.e. approaches to the said subject were analysed. The aim was to establish the extent to which the research has an interdisciplinary character which has become increasingly important in scientific circles over the recent past. The main contribution of this paper is that it provides insight into methods of investigations and dealing with prayer-books and catechisms applied by different sciences and professions.